The Characteristics of English Texts for Science and Technology and Translation Analysis Based on Functional Equivalence Theory: Taking Computer Texts as an Example - Lin, Wangyi (Journal of Theory and Practice of Contemporary Education, 2023)
From the perspective of functional equivalence theory, this article takes computer-related texts as the research object. Firstly, the characteristics of computer-related texts are explained, followed by a brief introduction to Eugene Nida's functional equivalence theory. Then, through example analysis, translation theory is combined with translation practice to summarize the application strategies of functional equivalence theory in computer-related texts. By collecting materials and analyzing relevant translations, it is hoped that this paper can provide reference for the translation of other technological texts.